Retrospective Analysis of the Safety and Cost Implications of Pediatric Contrast-Enhanced Ultrasound at a Single Center - Yusuf, Gibran T; Sellars, Maria E; Deganello, Annamaria; Cosgrove, David O; Sidhu, Paul S (American journal of roentgenology (1976), 2017)
Because of concern over medical ionizing radiation exposure of children, contrast-enhanced ultrasound (CEUS) has generated interest as an inexpensive, ionizing radiation-free alternative to CT and MRI. CEUS has received approval for pediatric hepatic use but remains off-label for a range of other applications. The purposes of this study were to retrospectively analyze adverse incidents encountered in pediatric CEUS and to assess the financial benefits of reducing the number of CT and MRI examinations performed. All pediatric (patients 18 years and younger) CEUS examinations performed between January 2008 and December 2015 were reviewed. All immediate reactions deemed due to contrast examinations were documented in radiology reports. Electronic patient records were examined for adverse reactions within 24 hours not due to an underlying pathologic condition. With tariffs from the U.K. National Institute of Clinical Excellence analysis, CEUS utilization cost ($94) was compared with the CT ($168) and MRI ($274) costs of the conventional imaging pathway. The records of 305 pediatric patients (187 boys, 118 girls; age range, 1 month-18 years) undergoing CEUS were reviewed. Most of the studies were for characterizing liver lesions (147/305 [48.2%]) and trauma (113/305 [37.1%]); the others were for renal, vascular, and intracavitary assessment (45/305 [14.8%]). No immediate adverse reactions occurred. Delayed adverse reactions occurred in two patients (2/305 [0.7%]). These reactions were transient hypertension and transient tachycardia. Neither was symptomatic, and both were deemed not due to the underlying disorder. The potential cost savings of CEUS were $74 per examination over CT and $180 over MRI. Pediatric CEUS is a safe and potentially cost-effective imaging modality. Using it allows reduction in the ionizing radiation associated with CT and in the gadolinium contrast administration, sedation, and anesthesia sometimes required for MRI.